Satsuma Mandarin Budget and Profitability Analysis for North Florida - Kevin R. Athearn; Peter C. Andersen; Brent V. Brodbeck; Lei Lani L. Davis; Clay Olson; Daniel K. Fenneman; Matthew C. Lollar; Derek Farnsworth; Michael Perez (EDIS)
This 16-page analysis written by Kevin R. Athearn, Peter C. Andersen, Bent V. Brodbeck, Lei Lani L. Davis, Clay Olson, Daniel K. Fenneman, Matthew Lollar, Derek Farnsworth, and Michael Perez and published by the UF/IFAS Food and Resource Economics Department provides research-based information and a description of satsuma mandarin markets, production costs, and potential returns for citrus growers who are considering establishing a satsuma grove in north Florida. Its purpose is to serve as a reference and model for growers to create their own enterprise budgets and make financial projections. An enterprise budget estimates revenues, costs, and net returns for a particular crop or farm enterprise to help growers assess the economic viability and risk of an enterprise, compare enterprises, and evaluate production or marketing changes. The budget and financial analysis may assist prospective and current satsuma growers, agricultural consultants, and lenders with planning and decision making. http://edis.ifas.ufl.edu/fe1030